2008
DOI: 10.1248/jhs.54.118
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Endocrine Disrupting Activities of Monohydroxylated Derivatives of 1-nitropyrene by Yeast Two-hybrid Assay

Abstract: Endocrine disrupting activities of three isomers of monohydroxylated 1-nitropyrene (1-NP) [3-, 6-, and 8-hydroxy-1-nitropyrenes (OHNPs)] were evaluated for the first time by yeast two-hybrid assay. OHNPs, which are not only metabolites of 1-NP but are also found in airborne particles, did not exhibit androgenic activity but exhibited estrogenic, antiestrogenic, and antiandrogenic activities. 6-OHNP showed the strongest estrogenic activity among the three OHNP isomers examined in this study. Concentrations of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The photochemical formation of hydroxynitropyrene isomers from 1-nitropyrene in diesel exhaust and airborne particles has been recently reported (Kameda et al, 2011). Most hydroxynitropyrene isomers as well as the diones (Benson et al, 1985) show lower mutagenicity (Manabe et al, 1985; Ball et al, 1984; Kameda et al, 2008) than the parent nitropyrene. Thus, the present results indicate that during the atmospheric transport of the DNPs, these strong bacterial mutagens can be phototransform into less biologically active intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…The photochemical formation of hydroxynitropyrene isomers from 1-nitropyrene in diesel exhaust and airborne particles has been recently reported (Kameda et al, 2011). Most hydroxynitropyrene isomers as well as the diones (Benson et al, 1985) show lower mutagenicity (Manabe et al, 1985; Ball et al, 1984; Kameda et al, 2008) than the parent nitropyrene. Thus, the present results indicate that during the atmospheric transport of the DNPs, these strong bacterial mutagens can be phototransform into less biologically active intermediates.…”
Section: Discussionmentioning
confidence: 99%
“…23,27,28) Recently, however, OHNPs such as 1-OH-3-NP, 1-OH-6-NP, and 1-OH-8-NP have been found to act as endocrine disruptors, i.e. they act as estrogenic, anti-estrogenic, and anti-androgenic compounds, 29,30) which may cause dysfunction of human and wildlife endocrine systems, abnormal development of reproductive systems, and immunodeficiencies. In view of the influence of OHNPs on human health, we need to learn more about their environmental concentration levels, sources and behavior.…”
Section: Atmospheric Formation Of Hydroxynitropyrenes From a Photochementioning
confidence: 99%
“…Several studies have found that most OHNP isomers have lower mutagenic activity than the parent 1-NP (Rosser et al, 1996;Manabe et al, 1985;Ball et al, 1985). Recently, however, OHNPs such as 1-OH-3-NP, 1-OH-6-NP, and 1-OH-8-NP have been found to act as endocrine disruptors: they act as estrogenic, anti-estrogenic, and anti-androgenic compounds (Kameda et al, 2008;Kameda et al, 2011a) that may cause dysfunction of human and wildlife endocrine systems, abnormal development of reproductive systems, and immunodeficiencies. In view of the influence of OHNPs on human health, we need to learn more about their environmental concentration levels, sources, and behaviors.…”
Section: Atmospheric Formation Of Hydroxynitropyrenes From a Photochementioning
confidence: 99%